Council of Europe: Guide on the decision-making process regarding medical treatment in end-of-life situations. (March 2016) - Veshi, Denard; Neitzke, Gerald
In this contribution, the "Guide on the decision-making process regarding medical treatment in end-of-life situations" published by the Committee on Bioethics of the Council of Europe has been analyzed by taking into consideration different perspectives, such as medical, ethical and legal views. In addition, some argumentations why this guide should also include physician-assisted suicide and euthanasia have been explained. The application of ethical principles and the balance between the patient's right to self-determination and the physician's duty of care have been studied under the general principle of fair distribution of public recourses in palliative care. Moreover, some examples from national legislation of some Western European countries have been given to illustrate and support these guidelines.